OPEN GOVERNMENT: KEY ISSUES IN SOUTH AFRICA - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2024)
This study aims to analyze key issues of open government in South Africa. Qualitative approaches and bibliometric analysis methods are used in this study. Data are sourced from the Google Scholar database collected using Publish or Perish (using keywords: South Africa transparency, South Africa participation, and South Africa public collaboration). These keywords are based on the main principles of open government. Data selection and completion using Mendelay, while obtaining a bibliometric map using VOSviewer. This study found 161 relevant South African open government articles, 618 total link strengths, 331 occurrences, and 113 topics. The dominant topics include public participation, transparency, local government, accountability, governance, participation, and regulation. While the latest and potential topics are social dialogues, public procurement, budgeting, integrated reporting, fiscal transparency, community participation, and legislation. South Africa has made 26 open government commitments and is currently focusing on 3 commitments (open data, transformative fiscal transparency, and beneficial ownership transparency). The commitment to open data and transformative fiscal transparency has great potential results to create a more open South Africa.